Social Ties and the Job Search of Recent Immigrants - Deepti Goel; Kevin Lang (Institute for the Study of Labor (IZA), 2016)
In this paper we highlight a specific mechanism through which social networks help in job search. We characterize the strength of a network by its likelihood of providing a job offer. Using a theoretical model we show that the wage differential in jobs found using networks versus those found using formal channels, decreases as the network becomes stronger. We verify this result for recent immigrants to Canada for whom a strong network is captured by the presence of a 'close tie.' Furthermore, structural estimates confirm that the presence of a close tie operates by increasing the likelihood of generating a job offer from the network rather than by altering the wage distribution from which an offer is drawn.
Keywords: J3; 330; job search; migration; networks